Femtosecond laser power absorption of glass - Satyal, Arun (Nanyang Technological University, 2020)
The linear and nonlinear absorption of power from a femtosecond laser pulse by a chemically strengthened glass, Gorilla Glass 2320, has been studied. Laser irradiation with short pulsed laser results in high-intensity laser interacting with the sample. As a result, even a transparent material for the given laser wavelength would undergo optical breakdown. In addition to linear absorption, the optical breakdown results in nonlinear absorption. Laser power absorption is quantified through the coefficients of absorption, viz. coefficient of linear absorption and coefficient of nonlinear absorption. Z-scan technique, being one of the widely adopted and effective experimental technique for optical characteristics quantification of material, has been adopted for the determination of these coefficients of absorption. In the Z-scan technique, to vary the laser beam intensity, a sample is translated along the axial direction of laser propagation passing through the focal plane. The laser power transmitted through the sample is recorded and analysed. When a sample is far away from the focal plane, the irradiated laser beam diameter is large and thus the laser beam intensity is low. In this low intensity region, the laser power is absorbed only through linear absorption. In contrast, when the sample is placed at or near the focal plane the incident laser beam diameter is small and thus the laser beam intensity is high. As a result of this high laser intensity, the laser power is absorbed through both linear and nonlinear absorption. However, existing formulation in the literature of the overall absorption coefficient, consisting of both linear and nonlinear absorption coefficients, is insufficient to account for the delineation of the linear and nonlinear absorption regions. Indeed, there is no consideration of the transition from one region to the other; the units for the overall, linear and nonlinear coefficients of absorption are also inconsistent. Here, a new formulation is proposed to account for the transition, and thus the delineation, between linear and nonlinear absorption. This is achieved through the introduction of the Nonlinear Absorption Threshold Intensity (NATI), which is defined as the laser power intensity at which the laser power absorption transits from linear laser power absorption to nonlinear laser power absorption. With the introduction of NATI, this formulation has a consistent unit for all the coefficients of absorption. Over a wide absorption range (linear and nonlinear), analyses demonstrate that this new formulation can describe the experimental observations far better than the existing formulation in the literature. Sample thickness has been an important parameter in the analysis of laser power absorption using Z-scan technique. In the previous studies, a sample has to be classified as a “thick” or a “thin” sample based on the Rayleigh length of the lasing system. Different analytical methods are applicable for either the “thin” or the “thick sample. There is this implicit assumption that the original spatial laser beam distribution will remain constant as it traverses a “thin” sample, and may not be for a thick sample. However, there is no justification provided on this classification if a sample is “thin” or “thick, nor the validity of the implicit assumption. This investigation shows that there is no physical basis for this classification. Indeed, it demonstrated that even for the so called “thin” sample, the spatial distribution of a laser beam changes as it traverses the sample thickness due to the nonlinear absorption of the laser power. The developed analytical approach here, together with the associated numerical procedure, can account for the changes of the spatial distribution of the laser beam as it traverses the thickness of the sample; this new approach can be applied to a sample of any thickness. For nonlinear absorption, laser power absorption increases nonlinearly and rapidly with laser power. However, existing methods of analysis ignored the temporal distribution of laser power within a single pulse. For a proper and rigorous representation of nonlinear absorption, this temporal variation must be capture for the computation of the nonlinear absorption coefficient. This investigation has developed the necessary formulation and associated numerical procedure for this purpose. Laser-induced plasma has been reported during laser-material interaction for different materials irradiated by ultrashort laser pulses. However, the effect of plasma formation on the study of laser power absorbed by the sample is lacking. Using high speed imaging, the laser-induced plasma was observed. It has been determined that the plasma decay time is less than 930 micro-seconds (µs). For the laser system with laser pulse duration of 130 femto-second (fs) and repetition rate of 1 milli-second (ms), this means that there is no laser-induced plasma interaction between two consecutive laser pulses. However, with the existing experimental limitations, laser-induced plasma interaction within the same pulse could not be ruled. It was further observed that plasma formation was significant at high laser power intensity; in contrast at low laser power intensity, no/insignificant plasma formation was observed. Thus, for proper analysis of laser power absorption and subsequent calculation of absorption coefficient, it is recommended to carry out the experiments at low power intensity where the effect of plasma formation, and thus the energy associated with it, can be neglected. Lastly, the obtained overall nonlinear absorption coefficients were independently verified through direct observation of temperature field during laser irradiation. Direct observation of temperature field was conducted using a thermal camera for in-situ measurements of temperature field during femtosecond laser irradiation of Gorilla Glass 2320. For the verification of overall absorption coefficients, a mathematical model for heat transfer during laser irradiation of Gorilla Glass 2320 was developed. The model accounts for femtosecond laser power absorption within Gorilla Glass 2320. Good correlations were obtained between the measured temperature fields with the predicted temperature fields as a result of heat energy absorption obtained through the overall absorption coefficients.